Climate variations over the southern Altai Mountains and Dzungarian Basin region, central Asia, since 1580 CE. (9th May 2019) - Oyunmunkh, Byambaa; Weijers, Stef; Loeffler, Joerg; Byambagerel, Suran; Soninkhishig, Nergui; Buerkert, Andreas; Goenster‐Jordan, Sven; Simmer, Clemens
Abstract: An improved knowledge of long‐term climatic variations over the Altai‐Dzungarian region will increase our understanding of the current climate and help to predict the effects of global warming on future water availability in this region. We sampled 77 Larix sibirica Ledeb. trees at upper and lower treelines in the southern Mongolian Altai mountains and reconstructed temperature and precipitation for longer periods than previous studies from this area. We reconstructed mean June–July air temperatures for the period 1402–2012 and June–December precipitation for the period 1569–2012 based on tree ring width chronologies. The temperature and precipitation reconstructions explain 39.7 and 41.3% of the respective station observation variance during the common periods. The precipitation reconstruction shows alternating wet and dry conditions during the Little Ice Age (1580–1874) followed by more stable conditions until a late 20th century wetting. The temperature reconstruction attributes the warmest period to the 20th century, which follows cooler periods related to volcanic and low solar activities during the Little Ice Age. Long‐term climatic variation and change over the Altai‐Dzungarian region is inferred from the analysis of the combined temperature and precipitation reconstructions for the common period 1580–2012. Accordingly, this region has become warmer since 1875 as the number of warm/moist and warm/dry years increased by 2 and 14%, respectively, while the number of cool/moist and cool/dry years both decreased by 8% compared to the Little Ice Age. Our findings also reveal a late 20th century cool and wet period, which has also been observed across other mountainous areas of China and Nepal. This period was most probably caused by volcanic‐induced cooling and coincided positive phases of the Arctic Oscillation and North Atlantic Oscillation promoting an intensified subtropical westerly jet and a positive summer rainfall anomaly over the Altai‐Dzungarian region. Abstract : Twenty‐five‐year low‐pass‐filtered time series of estimated June through December sum precipitation (black line), mean June–December NINO4 index (dark grey), mean January–March AO index (dashed black line), and mean February–April NAO index (light grey) over the period 1825–2012 (a); 25‐year centred moving correlation coefficients of the estimated precipitation with mean June–December NINO4 index (dark grey), mean January–March AO index (dashed black line), and mean February–April NAO index (light grey) over the same period (b).